Peran Perpustakaan dalam Implementasi Balanced Scorecard Lembaga Induknya: Studi Kasus di Kementerian Keuangan dan BPPT - Nurhayati, Muthia; Salim, Tamara Adriani; Gani, Fuad (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2017)
The purpose of this study is to determine how the role of libraries and the perception of librarians in the BSC implementation at the Ministry of Finance and BPPT. The method used is qualitative descriptive to determine the role of libraries and quantitative descriptive to know the perception of library staff. The results show the role of libraries in the implementation of the BSC lies in the perspective of internal processes in the strategy map parent institution. Ministry of Finance library employee perceptions of the BSC implementation is still considered inadequate by a factor of resources (staff, budget, and facilities). While the perceptions of BPPT library employee against BSC implementation is still considered inadequate by communication factor (clarity and consistency), disposition factor (incentives), and factor structure of the bureaucracy (standard operating procedures).